2022
DOI: 10.3390/membranes12090893
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission and Fusion: Molecular Mechanisms, Biological Functions, and Related Disorders

Abstract: Mitochondria are dynamic organelles that undergo fusion and fission. These active processes occur continuously and simultaneously and are mediated by nuclear-DNA-encoded proteins that act on mitochondrial membranes. The balance between fusion and fission determines the mitochondrial morphology and adapts it to the metabolic needs of the cells. Therefore, these two processes are crucial to optimize mitochondrial function and its bioenergetics abilities. Defects in mitochondrial proteins involved in fission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…In addition, it has been suggested that inhibitors of human carbonic anhydrase 3reduce abnormal pain caused by neuropathy in mice (37,38). Human FBXL4, a protein associated with autosomal recessive, multisystemic mitochondrial disorders, also showed an upward trend in the experimental group (39,40), and studies have shown that elevated FBXL4 can cause chronic pain and inhibit its mediated TRAF2 expression (41).The levels of NADH-ubiquinone oxidoreductase chain 4L differ between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been suggested that inhibitors of human carbonic anhydrase 3reduce abnormal pain caused by neuropathy in mice (37,38). Human FBXL4, a protein associated with autosomal recessive, multisystemic mitochondrial disorders, also showed an upward trend in the experimental group (39,40), and studies have shown that elevated FBXL4 can cause chronic pain and inhibit its mediated TRAF2 expression (41).The levels of NADH-ubiquinone oxidoreductase chain 4L differ between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…11,32 Mitochondrial fusion is regulated by three GTPase-dependent proteins, namely Mfn1 and Mfn2, which regulate outer membrane fusion, and OPA1, which regulates inner membrane fusion. Accumulating evidence indicates that deletion of Mfn1 and Mfn2 causes abnormal mitochondrial structure, 33,34 whereas Opa1 deletion mainly affects endosomal cristae formation, leading to impaired mitochondrial energy production. 35,36 Mitochondrial fission is mediated by Drp1, which oligomerically contracts and cleaves the mitochondrial membrane by binding to the ligand Fis1 of the outer mitochondrial membrane after phosphorylation at serine 616.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial self-regulation occurs through constant fission and fusion, providing energy for cellular homeostasis and regulating macroautophagy, calcium homeostasis, innate immunity, signaling and apoptosis. The relative balance of mitochondrial fission and fusion is essential to maintain the quality and function of mitochondria and is an important basis for normal cellular activity 7 , 39 . In contrast, mitophagy involves the sequestration and removal of damaged mitochondria from a cell through a specific autophagic pathway, thereby maintaining intracellular mitochondrial homeostasis 40 .…”
Section: Dynamic Regulation Of Mitochondriamentioning
confidence: 99%